DYNC1I1 Promotes the Proliferation and Migration of Gastric Cancer by Up-Regulating IL-6 Expression - Gong, Li-Bao; Wen, Ti; Li, Zhi; Xin, Xing; Che, Xiao-Fang; Wang, Jin; Liu, Yun-Peng; Qu, Xiu-Juan (Frontiers in Oncology, 2019)
Gastric cancer is one of the top five malignant tumors worldwide. At present, the molecular mechanisms of gastric cancer progression are still not completely clear. Cytoplasmic dynein regulates intracellular transport and mitotic spindle localization, and its abnormal function is crucial for tumorigenesis, promotes tumor cell cycle progression, and tumor migration. DYNC1I1 is an important binding subunit of cytoplasmic dynein.However, studies on DYNC1I1 in tumors are currently limited. In the current study, we found that high DYNC1I1 expression in gastric cancer is associated with poor prognosis and is an independent prognostic factor. DYNC1I1 promoted the proliferation and migration of gastric cancer cells both in vitro and in vivo. DYNC1I1 also upregulated IL-6 expression by increasing NF-κB nuclear translocation. Collectively, these data revealed an important role for the DYNC1I1-driven IL-6/STAT pathway in gastric cancer proliferation and migration, suggesting that DYNC1I1 may be a potential therapeutic target for gastric cancer.